2012
DOI: 10.1007/s00167-012-2213-1
|View full text |Cite
|
Sign up to set email alerts
|

Less blood loss under concomitant administration of tranexamic acid and indirect factor Xa inhibitor following total knee arthroplasty: a prospective randomized controlled trial

Abstract: The use of tranexamic acid could reduce acute blood loss significantly without any adverse effect resulted from drug interaction with concomitant use of indirect factor Xa inhibitor following TKA. Therefore, simple combination of these drugs can be recommended to reduce post-operative blood loss as well as to reduce DVT following TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 42 publications
3
41
1
Order By: Relevance
“…The above stated results are comparable with studies by charoencholvanich et al [17] , Gautam et al [18] and Lee et al [19] . These authors used similar dose regimen protocols as was used in this study.…”
Section: Blood Transfusionsupporting
confidence: 92%
“…The above stated results are comparable with studies by charoencholvanich et al [17] , Gautam et al [18] and Lee et al [19] . These authors used similar dose regimen protocols as was used in this study.…”
Section: Blood Transfusionsupporting
confidence: 92%
“…3 Without any effective thromboprophylaxis, the reported incidence of DVT after THA was 42% to 57%. 3 Considering the complications of DVT prophylaxis such as bleeding, deep inflammation, and prolonged wound drainage, 4,5 searching for some biomarkers that may predict DVT risk after THA will largely help individualized DVT prophylaxis with less complications in ONFH patients.…”
mentioning
confidence: 99%
“…In our study, similar to the studies in the literature. [31][32][33][34][35] It was found that the mean amount drain output & blood loss were 293 ml & 368 ml respectively in TXA Group however 20% of the patients were given PRBC transfusion. In Control Group mean amount of drain output & total blood loss calculated were 446 & 946 respectively, 56% patients required PRBC transfusion.…”
Section: Discussionmentioning
confidence: 99%